Applying qualitative design in research learning by doing - Kassim, Azilah; Dzakiria, Hisham (Universiti Utara Malaysia, 2006)
Qualitative research has never been a popular research design within Malaysian academics and research environment. Understanding the convention and fundamentals of conducting a qualitative research is important as it offers a different approach and generates a range of information of different quality from the quantitative approach. The compilation of the five articles included in this book has been carefully selected so that this book of reading represents different issues and problems that may arise when conducting a qualitative research. This book provides a good description of the research processes and issues that may also be encountered by other researchers especially those that are novice in qualitative research. The readings of the different research compiled in this book will hopefully contribute to the growing field of qualitative research as a research design among educators, researchers and professionals in Malaysia.